Learning Local Wisdom through the Symbols of Ma’nene’ Rituals in North Toraja: A Semiotic Perspective - M. Dalyan Tahir; Hunaeni Hunaeni; Sylver Tri Poetra (Utamax : Journal of Ultimate Research and Trends in Education, 2020)
This study examines the meaning of symbols and interpretations of local wisdom in ma’nene’ rituals in the Baruppu community of North Toraja Regency using a qualitative descriptive approach. Data regarding words and behavior in rituals were obtained through interview techniques, note-taking, recording, and documentation in the form of photos and videos. Data analysis used Pierce's semiotic theory. The results of this study indicate that the implementation of the ma’nene’ ritual is divided into two stages, namely: 1) Preparation (a) Ma'kongan ada', (b) Kapenomban pa'paranduk, (c) Manta'da, (d) Ma' pakande ada', (e) Umpasun bombongan; and 2) Implementation of (a) Ma'bungka', (b) Ma'kassa'i, (c) Massomba tedong, (d) Manglokko tedong sola bai, (e) Ma'pakande nene', (f) Mantutu', (g) Capenomban pa'paupu'. In carrying out the ritual, there are various symbols, including: (1) Tau-tau, (2) Bombongan, (3) Pangngan, (4) Kain ba'ru, (5) Tedong sola bai, (6) Bo'bo 'sola duku', (7) Punti leaves, (8) Tallang. Based on the semiotic analysis of the symbols in the ritual, several types of local wisdom were found, namely: (a) religious values, (b) brotherhood, and (c) unity.